2019
DOI: 10.1111/rda.13400
|View full text |Cite
|
Sign up to set email alerts
|

Follicular dynamics and colour Doppler vascularity evaluations of follicles and corpus luteum in relation to plasma progesterone during the oestrous cycle of Surti buffaloes

Abstract: Contents With an objective to evaluate the follicular dynamics and vascularity changes in follicles and corpus luteum, the ovaries of cyclic Surti buffaloes (n = 9) were examined daily sequentially by transrectal B‐mode and colour flow mode (CFM) ultrasonography starting from the day of oestrus till the onset of next oestrus. Higher proportion of buffaloes evidenced one‐wave cycle (66.66%) compared to two‐wave cycle (33.34%) with none showing a three‐wave cycle. The dominant follicle of the first follicular wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 41 publications
5
5
0
Order By: Relevance
“…A strong and positive correlation ( r = 0.8) was also found between the subjective and objective evaluation of analysis of CL vascularization by power flow Doppler method, which is not described in the literature in equine, which leads us to believe that, to facilitate the work of field veterinarian, only subjective assessment is sufficient in the analysis of vascular perfusion of the CL. Agreeing with other studies conducted in mares (Romano et al, 2015), goats (Balaro, Santos, Moura, Fonseca, & Brandão, 2017), sheep (Figueira et al, 2015), buffalo (Gaur & Purohit, 2019) and cows (Pugliesi et al, 2017), in our study it was possible to prove the proportional growth between the vascularization of P4 and CL. However, some mares presented with dosage of P4 at least 5.3 ng/ml and no luteal vascularization was observed.…”
Section: Discussionsupporting
confidence: 88%
“…A strong and positive correlation ( r = 0.8) was also found between the subjective and objective evaluation of analysis of CL vascularization by power flow Doppler method, which is not described in the literature in equine, which leads us to believe that, to facilitate the work of field veterinarian, only subjective assessment is sufficient in the analysis of vascular perfusion of the CL. Agreeing with other studies conducted in mares (Romano et al, 2015), goats (Balaro, Santos, Moura, Fonseca, & Brandão, 2017), sheep (Figueira et al, 2015), buffalo (Gaur & Purohit, 2019) and cows (Pugliesi et al, 2017), in our study it was possible to prove the proportional growth between the vascularization of P4 and CL. However, some mares presented with dosage of P4 at least 5.3 ng/ml and no luteal vascularization was observed.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, the mean serum progesterone concentrations were the lowest during the peri-estrus phase, which increased through early luteal phase to a maximum concentration during mid luteal phase in cyclic Surti buffaloes. These results were in agreement with earlier observations (Mondal et al, 2010;De Tarso et al, 2017;Gaur and Purohit, 2019). The cyclic pattern of circulatory progesterone concentrations follows the known changes in corpus luteum function in buffalo during estrous cycle.…”
Section: Follicular/luteal Biometry and Endocrine Profilesupporting
confidence: 93%
“…The characteristics of follicular dynamics observed in cyclic Surti buffaloes indicated that 33.33% (n=2) and 66.66% (n=4) of buffaloes had one-and two-waves of follicular development, respectively, while in early pregnant buffaloes one-and two-waves of follicular patterns were in equal proportion (50.00% n=3 each, Table 1, 2). Similar predominant two-wave pattern of follicular development in buffaloes ranging from 53.0 to 83.3% was reported by Baruselli et al (1997), Presicce et al (2005), Noseir et al (2014) and Gaur and Purohit (2019). However, 62.5% of one-wave pattern in water buffaloes (Awasthi et al, 2006) and 53.6% and 83.3% of three wave pattern in Egyptian buffaloes (Barkawi et al, 2009) and in Graded Murrah buffaloes (Satheshkumar et al, 2011) were also reported.…”
Section: Follicular Dynamicssupporting
confidence: 69%
“…A recent study evaluated the vascularity of ovarian follicles and the corpus luteum during the estrous cycle in Surti buffaloes (Gaur & Purohit, 2019) [14] . Studies on umbilical vasculature and blood flow to the uterus in buffalo during gestation are very few (Varughese, Brar & Dhindsa).…”
Section: ~ 461 ~mentioning
confidence: 99%